Utilization of Different Substrates on Goldfish (Carrasius auratus) Seeds Productivity - Yusanti, Indah Anggraini; Sofian; Tri Iswani (Universitas PGRI Palembang, 2025)
The success of goldfish (Carrasius auratus) spawning is influenced by several factors, including the substrate media for fish spawning. This study aims to analyze the utilization of different substrates on the productivity of goldfish which includes the number of eggs attached to the substrate, the number of fertilized eggs, the number of eggs that hatch, and the survival of goldfish. The research method used a completely randomized design (CRD) with 4 treatments and 3 replications, including P1 coconut coir substrate, P2 knitting yarn substrate, P3 Hydrilla sp substrate, and P4 Pistia stratiotes L substrate. The results showed that a lot of goldfish eggs attached to the apu-apu substrate (treatment P4) of 1,959 eggs, the highest number of fertilized eggs was obtained on the substrate Hydrilla sp (treatment P3) of 65.65%, the highest number of eggs hatched on the substrate Hydrilla sp. (P3 treatment) was 78.54%, the highest survival rate was on Pistia stratiotes L substrate (P4) was 85.97 and the results of water quality analysis during the study supported the productivity of goldfish seeds.